Sustainable Production of the Cyanophycin Biopolymer in Tobacco in the Greenhouse and Field - Huckauf, Jana; Brandt, Boudewijn P.; Dezar, Carlos; Nausch, Henrik; Hauerwaas, Antoniya; Weisenfeld, Ursula; Elshiewy, Ossama; Rua, Melina; Hugenholtz, Jeroen; Wesseler, Justus; Cingiz, Kutay; Broer, Inge (Frontiers in Bioengineering and Biotechnology, 2022)
The production of biodegradable polymers as coproducts of other commercially relevant plant components can be a sustainable strategy to decrease the carbon footprint and increase the commercial value of a plant. The biodegradable polymer cyanophycin granular polypeptide (CGP) was expressed in the leaves of a commercial tobacco variety, whose seeds can serve as a source for biofuel and feed. In T0 generation in the greenhouse, up to 11% of the leaf dry weight corresponded to the CGP. In T1 generation, the maximum content decreased to approximately 4% dw, both in the greenhouse and first field trial. In the field, a maximum harvest of 4 g CGP/plant could be obtained. Independent of the CGP content, most transgenic plants exhibited a slight yield penalty in the leaf biomass, especially under stress conditions in greenhouse and field trials. After the harvest, the leaves were either sun dried or ensiled. The resulting material was used to evaluate the extraction of CGP compared to that in the laboratory protocol. The farm-level analysis indicates that the extraction of CGP from tobacco plants can provide alternative income opportunities for tobacco farmers. The CGP yield/ha indicates that the CGP production in plants can be economically feasible depending on the cultivation and extraction costs. Moreover, we analyzed the consumer acceptance of potential applications associated with GM tobacco in four European countries (Germany, Finland, Italy and the Netherlands) and found unexpectedly high acceptance.